Un-iconic - Paolo Barucchieri (Oz, 2010)
I believe the 20th century marks a period of extraordinary scientific discoveries that have ignited transformations in all areas of human endeavor. These advances, and what Toynbee describes as “the welfare of the whole human race as a practical objective” were, unfortunately, in contrast with the intense speculation and competition that characterized the economic drive of the 20th century.